Pengaruh Teknik Self Management Berbasis Konseling Islami terhadap Minat Belajar Siswa - Salsabila, Sarah; Mujib, Abdul; Eryanti, Devi (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2024)
This study aims to determine the process of Islamic counseling self-management techniques, determine the condition of student interest in learning and determine the effect of self-management techniques based on Islamic counseling to increase student interest in learning. The research method uses a quantitative method of pre-experimental one shot case study. Data collection techniques were carried out through unstructured interviews, observation, questionnaires, and documentation. The total population is 222 students, while the number of samples is 22 students. Hypothesis test using simple linear regression test. Sampling using purposive sampling technique. The results of this study are Islamic counseling self management techniques have an effect on increasing student interest in learning. Referring to the statistical results of a simple linear regression test, the value of sig = 0.000 is obtained, which means that if sig < 0.05 then Ha is accepted and H0 is rejected. The effect of Islamic counseling on self-management techniques on students' interest in learning is 73.9%. So, it can be concluded that the greater the counseling process is carried out, the greater the increase in student interest in learning.